PENGARUH BUDAYA ORGANISASI DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. FIFGROUP CABANG MARELAN - Putra, Ardian Syah; Nasution, M. Amri; Rahim, Rani (Universitas Dharmawangsa, 2024)
This study aims to explain the influence of organizational culture and employee commitment on employee performance. The sampling technique used in this research involved 63 respondents who are employees of FIFGroup Marelan Branch. The results of the first hypothesis test show that the organizational culture variable yielded t-count > t-table = 3.646 > 2.000. Thus, it can be concluded that organizational culture has a significant positive effect on employee performance at PT. FIFGROUP Marelan Branch. This indicates that the more appropriate the organizational culture, the better the employee performance. In the second hypothesis test, the employee commitment variable yielded t-count > t-table = 3.089 > 2.000. Therefore, it can be concluded that employee commitment has a significant positive effect on employee performance at PT. FIFGROUP Marelan Branch. This indicates that the stronger the employee commitment, the better the employee performance. The results of the F-test in this study show a significance value of 0.000, which is smaller than the alpha value of 5% (0.05), or F-count > F-table = 32.962 > 3.15. Therefore, it can be concluded that organizational culture and employee commitment simultaneously have a significant effect on employee performance at PT. FIFGROUP Marelan Branch.